(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nationsare people with different ways of life and society. They live somewhere in a certain place. They have their own customs, traditions, religiousbelief,etc. What makes them different from other national communities. The literacy of tribes is generally below the literacy rate of most people of the world.Accordingto the 2011 population the national literacy rate (59.00%) is found to be significantly lower than the national literacy rate (73.00%). This paperfocuses on educating the tribal children of the nation and the challenges they face